Prevalence of polycystic ovaries among patients with hirsutism and menstrual abnormalities - Rasool, Shazia; Dar, Lubna Riaz; Hameed, Abdul (Journal of Pakistan Association of Dermatologists, 2016)
Background Polycystic ovaries are considered to be the most frequent cause of hirsutism with its prevalence of 10% of woman of reproductive age group. Polycystic ovarian syndrome (PCOS) reflects multiple potential etiologies and variable clinical presentations Â Objectives To investigate the prevalence of polycystic ovaries among patients with hirsutism and menstrual abnormalities (oligo- or oligohypomenorrhea) and to correlate presence of hirsutism with BMI, polycystic ovaries, ovarian volume and biochemical markers. Â Patients and methods All patients who presented with oligo- or oligohypomenorrhea or hirsutism either in outpatient clinic of Obstetrics and Gynecology, Shalamar Hospital or a private laser clinic were enrolled in study. Patients who had hirsutism with normal menstrual cycle were excluded from study. Enrolled patients were categorized into two groups on basis of hirsutism, group 1: oligomenorrhea/oligohypomenorrhea with hirsutism and group 2: oligomenorrhea/oligohypomenorrhea without hirsutism. A detailed clinical history, clinical examination, hormonal profile and abdominopelvic ultrasound were done in all patients. SPSS version 16 was used for statistical analysis. Â Results Out of 90 patients who enrolled in the study, 10 did not report back, so were excluded from study. Out of 80 patients with menstrual problem, 55 (68.7%) had hirsutism (group 1) and 25 (31.3%) had no hirsutism (group 2). Prevalence of polycystic ovaries was 815% among patients with hirsutism and oligo/oligohypomenorrhea (group 1) as compared to 44% in patients with oligo/oligohypomenorrhea without hirsutism (group 2). Ovarian volume >10ml and BMI were not statistically significant among both groups. Regarding hormonal profile, serum LH/FSH ratio and testosterone levels were significant among patients with hirsutism as compared to without hirsutism. Â Conclusion Prevalence of polycystic ovaries by morphology, FSH/LH ratio and serum testosterone are significantly present among patients with oligo/oligohypomenorrhea and hirsutism as compared to those with oligo/oligohypomennorhea without hirsutism. However Ovarian volume and BMI are not statistically significant among both groups. Â